The response of a structural target to oblique fragment and blast loading - Van Der Merwe, Pierre (Department of Mechanical Engineering, 2025)
An improvised explosive device (IED) can be defined as a homemade bomb which is used to target humans and structures [1]. IEDs commonly have dual damaging effects, a high-pressure blast wave that propagates outwards from the point of detonation as well as blast induced fragments. The blast induced fragments include the casing of the IED and added components to increase its lethality and destructive power. Examples of these added components can include but not limited to nails, pieces of glass, nuts, bolts and ball bearings [2]. Fragments, released upon the detonation of the device, are propelled outwards at high velocities and different directions with devastating effects on structures or human lives. Investigating the fragment effect is vital to develop better protection. Two sets of experiments were undertaken in this study, projectile impact experiments and blast experiments. The impact loading of an IED was investigated by performing projectile impact experiments to infer the average impact velocity of the ball bearing during the blast experiments. Impact loading caused by IEDs is complex and often contains numerous fragments. Typical fragments were simplified to a ball bearing propelled using a two-stage gas gun towards a Domex 700 steel target plate. The velocity of the ball bearing and the orientation angle of the target plate was varied. A numerical study was undertaken to further study oblique impact of a ball bearing on a Domex 700 target plate and to investigate experimental uncertainty. Blast experiments were carried out using a cylindrical charge with an embedded ball bearing representing a simplified IED to investigate the response of a target plate experiencing oblique detonation by varying the angle of the explosive. The mass and geometry of the explosive and the placement of the ball bearings were kept constant. For the projectile impact experiments, it was found that an increase in the target plate orientation angle was associated with a decrease in the maximum deflection experienced by the target plate. In contrast, for the blast experiments, the target plate deflection increased as the orientation angle of the explosive charge increased up to 15°. The effect of the orientation angle of the explosive charge decreases for charge orientation angles larger than 15°.